Manajemen Project Based Learning dalam Meningkatkan Keterampilan Abad 21 di Sekolah Penggerak Jenjang Dasar - Marsithah, Iis; Yanti, Hera; Idawati (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
This study aims to analyze Project Based Learning planning, Project Based Learning implementation and Project Based Learning evaluation conducted by SD Negeri 21 Bireuen in improving 21st century skills for students and studying the challenges faced in Project Based Learning management. This research uses a qualitative approach with a descriptive method. Data collection through observation techniques, interviews and documentation review. The research subjects were the principal, deputy principal for curriculum, and two class teachers in Phase C. Research results: 1) Project based learning planning has gone well. The activities start from teacher council meetings, socializing project activities to parents. Planning, including: analysis of material characteristics from learning outcomes, determination of goals, conditions, time, compiling steps of project based learning activities, evaluating learning and making worksheets and 6C skill assessment formats. 2) The application of the Project Based Learning model related to improving 6C skills is going well, judging from the steps of activities used according to the procedures of the Project based learning concept. 3) Project based learning evaluation went well. It can be seen from the acquisition of scores on teacher activities to achieve very good predicates, and 4) The challenges faced are that school principals need teachers to be more creative, require a lot of media, costs and time in implementation, so there needs to be breakthroughs and innovations so that the project runs well.